Knowledge, attitude and practice of research ethics among medical faculty in a teaching hospital - Munoli, Swetha; G., Niveditha; R., Deepthi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To assess the knowledge, attitudes and practice of medical faculty regarding research ethics and research ethics committees (RECs). Methods: A cross-sectional, questionnaire-based study was conducted in ESIC medical colleges in Bangalore among faculty using a validated questionnaire. Questions were designed to assess the knowledge, attitudes and practice of medical faculty regarding research ethics and research ethics committees. Statistical analysis was done using descriptive statistics and chi-square tests. Results: Majority (76%) of faculty had not undergone training in research ethics. Less than half of the participants answered correctly to a question on guidelines in research ethics, 60% responded correctly to question on research involving children. Majority responded correctly to question on role of a research ethics committee and confidentiality, informed consent and to question on composition of Institutional Ethics Committee. 68% taught that ethical review of research by an ethics committee would delay research. >90% were favourable towards research ethics training. Faculty held attitudes regarding certain research ethics practices that were not optimal, 96% believed that it is okay to fabricate data, 68% taught that if no surrogate is available to give informed consent for vulnerable groups, they could still be included. Conclusions: We conclude that among the medical faculties participating in our study, there is acceptance of RECs and training in research ethics, while there are knowledge gaps in research ethics guidelines, research involving children. There is need to train researchers and students to make them aware about various aspects of research.